Czy przed piractwem domenowym można się bronić? Formy naruszeń i cywilnoprawne środki ochrony przed nieuprawnionym korzystaniem ze znaków towarowych w domenie internetowej - Trzeciak-Wach, Karolina (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The subject of the consideration is mainly connected with the plans of launching new names of generic Top Level Domains gTLD. The author tries to present some possibilities of law infringement which could be caused in the future, because of these operations. The aim of this paper is to show the legal solutions to help with the domain pirates infringements.The plurality of the new gTLD is the chance for domain pirates. In the present literature there are distinguished many forms of domain pirates such as: cybersquatting, cybertyping, cyberwildcatting and cybersmearing. All of them could be a form of using trademarks without rights to them. First of all, the author discusses the circumstances of trademarks infringement under Industrial Property Law. The author also comments on the types of activities which constitute unfair competition in relation to the use of trademarks in domains and suppression of Unfair Competition Act. In the analysis, there are also presented the ways of alternative dispute resolution and the new procedure against infringement establishes by ICANN.
Keywords: domena; piraci; znaki towarowe; naruszenie; alternatywa